Keadilan Dipersimpangan: Menelusuri Tantangan Dan Peluang Di Sistem Hukum Modern - Fikri Ferdiansah; M. Fachri Sidiq; Richad Richad (Lembaga Pengembangan Kinerja Dosen, 2024)
This journal discusses the phenomena of justice that are intersecting in the modern legal system. Using theoretical research methods, the study explores the many challenges and opportunities that arise as a result of the complexity and dynamics of the evolution of today's legal systems. The theoretical analysis in this journal identifies paradigm shifts, inequalities in access to justice, and normative changes as crucial elements that affect the integrity of the legal system. With the depth of this research, it is expected to provide in-depth insight into the legal reforms needed to create more effective and equitable justice in modern societies.